New friendships and old feuds: relationships between innate lymphoid cells and microbial communities. Issue 3 (22nd January 2013) - Philip, Naomi H; Artis, David
Abstract : Mammalian barrier surfaces, including the skin, lung and intestine, are constantly exposed to environmental stimuli, including beneficial and pathogenic microbes, dietary substances and non‐organic materials. At these anatomical sites it is essential to maintain barrier integrity to promote tissue homeostasis and prevent local and systemic inflammation. As such, changes in the composition and localization of commensal bacteria are closely associated with inflammatory, metabolic and infectious disease in mammals. Cells of the innate and adaptive immune systems have a crucial role in the tight regulation of host‐commensal relationships. A recently described family of immune cells, termed innate lymphoid cells (ILCs), contributes to inflammation, modulates adaptive immunity and regulates wound healing and tissue regeneration. ILCs are present at barrier surfaces, and thus are in close proximity to environmental antigens, including commensal bacteria. The composition and localization of microbial communities have a profound impact on immunity at barrier surfaces as well as at distant sites. This review will summarize the phenotypic characteristics of ILC family members and discuss recent findings about the interactions between ILCs and the microbiota in the contexts of homeostasis, immunity, inflammation and tissue organization and repair. Abstract : The March 2013 issue of Immunology and Cell Biology contains a special feature that focuses on the role of the intestinal epithelial barrier and innate immune cells, examines their crosstalk with the commensal flora, and assesses their contribution to intestinal immunity in health and disease. There is a complexity of interaction among these distinct components and the Reviews of this special feature examine, unravel and investigate the action and reaction in the intestinal homeostasis‐perturbation cycle. Further background information on this important topic is available through the accompanying web focus which links to related articles from across Nature Publishing Group.